Impulsive noise of partial discharge and its impact on minimum distance-based precoder of MIMO system - Madi, Ghadir; Vrigneau, Baptiste; Pousset, Yannis; Vauzelle, Rodolphe; Agba, Basile L. (Proceedings of the ... European Signal Processing Conference (EUSIPCO), 2010)
Impulsive interference has been measured recently in some wireless communication environments. By using measured data of partial discharge, we show in this paper that the Middleton Class A model can approximate the impulsive noise in an electricity substation better than the Gaussian noise. The measured data was obtained from Hydro-Québec's Research Institute in cooperation with ETS (École de technologie supérieure of Montreal). We derive an extension of Middleton Class A model for multi-antenna systems. Using this model with estimated parameters from measured data, we evaluate the performance of two linear MIMO precoders with two spectral efficiencies (4 bit/s/Hz and 8 bit/s/Hz). The max-d min precoder optimizes the minimum Euclidean distance of the received constellation and the max-SNR or single beamforming maximizes the received SNR.